2008
DOI: 10.1111/j.1365-2710.2008.00962.x
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil citrate as a phosphodiesterase inhibitor has an antioxidant effect in the blood of men

Abstract: Treatment of blood with 100 mg sildenafil citrate has protective effects on oxidative stress by inhibiting free radical formation and by supporting antioxidant redox systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 21 publications
2
36
0
3
Order By: Relevance
“…26 One placebo-controlled study found that 100 mg sildenafil citrate had a beneficial effect on the serum oxidative status of subjects without any health problems; the effect lasted for about a day. 11 Another study reported the same conclusion in an animal model of passive-smoking-induced ED. 12 Our results on the oxidative status of patients with ED support these findings for tadalafil citrate; additionally, although we did not measure data more than 2 h after drug administration, we propose that the reduction in serum oxidative stress may last more than a day, given that tadalafil citrate has a longer serum half-life than sildenafil citrate.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…26 One placebo-controlled study found that 100 mg sildenafil citrate had a beneficial effect on the serum oxidative status of subjects without any health problems; the effect lasted for about a day. 11 Another study reported the same conclusion in an animal model of passive-smoking-induced ED. 12 Our results on the oxidative status of patients with ED support these findings for tadalafil citrate; additionally, although we did not measure data more than 2 h after drug administration, we propose that the reduction in serum oxidative stress may last more than a day, given that tadalafil citrate has a longer serum half-life than sildenafil citrate.…”
Section: Discussionmentioning
confidence: 62%
“…Studies on the beneficial effects of PDE5 inhibitors on endothelial functions and their contribution to vascular repair have provided justification for the expansion of the indication spectrum. 11,12,20,21 Paradoxically, the associations of PDE5 inhibitors usage and some life-threatening events, such as acute MI and stroke, in connection with some disorders, such as cardiac arrhythmias, hypo/hypertension, are related to the cardiac and neurovascular systems. 7,8 Nevertheless, recent reports strongly suggest that there is no increase in the incidence of acute MI or death rates during sexual activity while using PDE5 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that oxidative stress increases the expression of PDE5 in the cardiomyocytes of failing hearts (Lu et al, 2010) and sildenafil attenuated oxidative stress by inhibiting free radical formation and by facilitating antioxidant redox systems (Bivalacqua et al, 2009;Perk et al, 2008). One of the mechanisms of action of PDE inhibitors might be to reduce oxidative stress levels, as PDE levels are up-regulated in conditions such as pulmonary hypertension, chronic HF and right ventricular hypertrophy (Corbin et al, 2005;Forfia et al, 2007;Nagendran et al, 2007) and oxidative stress mediates the dysfunctional NO-cGMP-PKG signalling in cardiovascular disease.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…a Reversion of the tumorigenic phenotype by GCC is generalizable, reproduced in numerous human and mouse colon cancer cell lines. a Of significance, activation of GCC signaling suppresses ROS production, a reflecting increased function of the electron transport chain [70][71][72] or increased production of ROS scavengers, [73,74]and promotes genetic stability. a Interestingly, a study [10] using Apc Min/+ mice suggested that supplementation of uroguanylin significantly suppressed intestinal tumorigenesis, including tumor initiation and progression.…”
Section: Targeted Prevention and Therapy For Colorectal Cancermentioning
confidence: 99%